(untitled) (Research, Society and Development, 2021)
Objective: To understand the narratives of professionals about the networks of petitionand commitments and their articulation with the practices performed in Primary Health Care and Psychosocial Care. Methodology: Qualitative study based on the search for confrontations and complementarities present in the subjects’ reports, carried out in the UAPS with complete teams - SER VI, CAPS Geral and NASF- AB of this same regional VI. Results: The results that emerged from the thematic analysis of the data are expressed in the categories presented as "WE": (1) The care between mental health and the family health strategy an invitation to the sensitive look through the Petition Networks and Commitment; (2) The individuals’ understanding of the Networks of Petitions and Commitments; (3) Absence and/or weaknesses of the petition network and commitments between care devices (ESF - CAPS- General). Discussion: The potentiation of mental health care to the user presupposed the establishment of a sensitive relationship between professionals and/or workers in the sense of care, as well as among supporters of other care units, with apprehension of intersubjectivity in this shared universe. Final Considerations: Gradually brought changes in concept during the meetings and the inclusion of reflections around the relationships that can establish bonds and shares built by them, generating comprehensive and sensitive care as an effective form of care.